Correlation between CD44 expression on histopathological grading, metastasis, survival overall (SO) and disease free survival (DFS) on women breast cancer - Ahmad Syaifudin; Septiman Septiman; Indra Indra; Prihantono Prihantono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Breast cancer is one of the health problems in the world. In Indonesia, it washighest prevalence of cancerin 2018. CD44, a non-kinase transmembrane glycoprotein, plays an important role in cancer development and progression.It isresponsible for mediating of the adhesion between adjacent cells andalsobetween cells and the extracellular matrix. The aim of study was to investigatethe relationship between the CD44 expressionand histopathological grading, metastasis, overall survival (OS) as well as disease free survival (DFS)in breast cancer patients.Thiswas a retrospective cross sectional studyusing data on medical records of breast cancer cases at Dr. Wahidin Sudirohusodo General Hospital, Makasarfrom 2016 to 2018. Examination of CD44 expression were performed from paraffin block samples.Data of the CD44 expression and medical records obtained were then presented in tables and statistically analyzed using chi-squared and Kaplan–Meier survival analysis.No significantly relationship between the CD44 expression and histopathological grading was reported (p>0.05). However, significantly relationship between the CD44 expression and metastasis war reported (p<0.01). Patients with metastasis havinghigh CD44 expression was significantly higher (90%) than those patients without metastasis (60%) (p<0.01). No significantly relationship between the CD44 expression and OS or DFS was reported (p>0.05). In conclusion, there isrelationship between CD44 expression and metastasis in the breast cancer patients. However, there is norelationship between CD44 expression and histopathological grading, OS as well as DFS.